Biotemplating synthesis of organized structures inspired by biological processes. (August 2022) - Liu, Yin; Zhu, Chenglong; Wan, Fuqiang; Fang, Weijian; Xue, Bingyu; Zheng, Zhuozhi; Ping, Hang; Xie, Hao; Wang, Hao; Wang, Weimin; Fu, Zhengyi
Abstract: The hierarchical structures of biological materials endow them with excellent mechanical performance and specific functionality. Interestingly, structures are formed under the functions of biological systems under mild conditions, which inspires the synthesis and fabrication of artificial materials at room temperature. During the formation of biological structures, biotemplating effects play critical roles, such as confined environments, surface functional groups, molecular conformation, and self-assembly behavior. Based on these functional characteristics, many studies have focused on choosing biological templates that are abundant in nature and easy to obtain or to design customized biological templates based on pristine biotemplates to realize the formation of organized structures and the optimized performance of materials. In this review, we summarize the four types of biotemplates, including collagen, cellulose, viruses, and bacteria, for the synthesis of organized structures. Benefiting from this review, the effects of biotemplating on artificial material synthesis will receive more attention from researchers and will contribute to the synthesis of new materials and structures. Graphical abstract: Image, graphical abstract